EFEKTIFITAS POS BANTUAN HUKUM PENGADILAN SEBAGAI PEMBERI LAYANAN BANTUAN HUKUM CUMA-CUMA PADA PERKARA PIDANA PADA PENGADILAN NEGERI PEKANBARU - RAJAGUKGUK, TODIMAN; Indra, Mexsasai; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Each of Indonesian society litigants in civil and criminal courts are entitled to receive legal aid services .. Legal Aid Post which was then known as Posbakum an existing post in every district court in Indonesia in shape by the Supreme Court of the Republic of Indonesia on duty to provide legal aid services to the underprivileged people who are blind to the law in court. The purpose of this thesis, namely: First, Service provision of legal aid by the Legal Aid Post as legal aid free of charge in the District Court of Pekanbaru, Second, obstacles to the implementation of the provision of legal aid by the Postal Assistance law as legal aid free of charge in case criminal in Pekanbaru District Court, Third, efforts made to overcome the obstacles the implementation of legal aid by the Legal Aid Post as giving free legal aid in Pekanbaru District Court..From the results of research and discussion, there are three main things that can be inferred. First, the district court legal aid Posbakum giving free legal services in criminal cases in the district court partially Pekanbaru running legal services and other legal services has never been implemented. Second, in the implementation of the provision of legal services encounter obstacles. Third, efforts were made in overcoming obstacles to the implementation of the provision of free legal services to the community can not afford in Pekanbaru District court is melakasanakan effort to minimize bottlenecks in the provision of legal aid serv Posbakum Pekanbaru District Court. Suggestions, First ZIP legal aid providing quality legal services to the disadvantaged communities although faced with barriers which give rise to legal services is less effective and efficient; Second, the Giver of legal services at the court must further improve socialization or legal counseling to the community litigants in Court, Third, Giver of government and community legal services in order to work together again in the improvement of legal aid services.Keywords: Effectiveness - Posbakum- -Cuma Legal Aid Services of Charge